PENGARUH UKURAN KAP, KONDISI KEUANGAN PERUSAHAAN,OPINI AUDIT TAHUN SEBELUMNYA, PERTUMBUHAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN - Feronike, Nadya Ike; Budisantoso, Totok (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
The aim of this research is to analyze the efect of public frm size, the fnancial condition of the company, the previous year audit opinion, and growth of the company to audit opinion for going concern. The survival of the business is always associated with the ability of management to manage the company in order to survive. Survival can be seen from the fnancial condition and growth of these companies. Problems going concern of a company is very important to know and be disclosed, so that the company can take further action and consideration of appropriate decisions to maintain the viability of its business so as to avoid bankruptcy.Samples were taken by using purposive sampling method manufacturing the food and beverage industry groups listed on the Stock Exchange in the study period is from 2009-2012 and had complete data associated with the variables in the study period 2009- 2012. Hypothesis testing using the p value Wald on Logistic Regression. Te results of this study indicate that frm size and fnancial condition did not signifcantly afect Going Concern Audit Opinion, while the ratio of audit opinion received in the previous year Sales Growth Ratios and auditees signifcant efect on Going Concern Audit Opinion.Keywords: fnancial condition of the company, going concern opinion, growth of the company, previous year audit opinion, public frm size.